A double point mutation in PCL-γ1 (Y509A/F510A) enhances Y783 phosphorylation and inositol phospholipid-hydrolyzing activity upon EGF stimulation - Chung, Sang-Hee (Korean Society for Biochemistry and Molecular Biology, 2010)
Growth factor stimulation induces Y783 phosphorylation of phosphoinositide-specific PLC-γ1, and the subsequent activation of this enzyme in a cellular signaling cascade. Previously, we showed that a double point mutation, Y509A/F510A, of PLC-γ1, abolished interactions with translational elongation factor 1-α. Here, we report that the Y509A/F510A mutant PLC-γ1 displayed extremely high levels of Y783 phosphorylation and enhanced catalytic activity, compared to wild-type PLC-γ1, upon treatment of COS7 cells with EGF. In quiescent COS7 cells, the Y509A/F510A mutant PLC-γ1 exhibited a constitutive hydrolytic activity, whereas the wild-type counterpart displayed a basal level of activity. Upon treatment of COS7 cells with EGF, the Y783F mutation in Y509A/F510A PLC-γ1 (Y509A/F510A/Y783F triple mutant) cells also led to an enhanced catalytic activity, whereas Y783F mutation alone displayed a basal level of activity. Our results collectively suggest that the Y509A/F510A mutant is more susceptible to receptor tyrosine kinase-induced Y783 phosphorylation than is wild-type PLC-γ1, but no longer requires Y783 phosphorylation step for the Y509A/F510A mutant PLC-γ1 activation in vivo.